Design of Inverted F-Shape Antenna at 2.35 GHz for S-Band Applications - N. Adel, Randa; H. Khidhir, Ali (Al-Nahrain Journal of Science, 2022)
In this work, a simulation model of planar inverted F antenna (PIFA) will be presented with the radiating plate that has been connected to ground plane that has been accompanied by shortening plate and the FR4 substrate between ground plane and radiating plate. Where PIFA was built using computer simulation technology (CST) for the studio microwave (2019 release). The simulation model has been studied for return loss (S-parameter), bandwidth (BW), voltage standing wave ratio (VSWR), and input impedance (Zin) which are -21.875406dB, 301MHz, 1.1752855, and 50 W, respectively. The simulation results showed that the PIFA component covers a wide frequency band ranging between 2.202 and 2.504 GHz, which can be used in Bluetooth, Wi-Fi, and Long Term Evolution (LTE) applications that are used in the fourth generation cellulares communications.